Upaya Guru BK dalam Meningkatkan Pemahaman tentang Kesehatan Reproduksi Remaja di SMK Ma’arif NU Kajen - Atika Maulida Rizka; Dini Rakhmawati; Agus Setiawan (Departement of Mathematics Education, 2024)
The background that prompted this research was students who had a poor understanding of reproductive health. This is due to the provision of reproductive health services by guidance and counseling teachers which is less than optimal. The aim to be achieved in this research is to determine the efforts of bk teachers in increasing understanding of adolescent reproductive health at MA'ARIF NU KAJEN Vocational School. The method used in this research is a qualitative research method. The respondents in this study were 1 guidance and counseling teacher and 5 students. The data in the research was obtained through interviews and documentation. Based on the results of research that researchers have conducted, the conclusion is that the efforts of bk teachers to increase understanding of adolescent reproductive health are by providing classical guidance services, individual counseling and collaboration or collaboration with various parties.